Designing A 3-Dimensional Campus Brochure Application Based On Augmented Reality - Dayat, Abd. Rachman; Angriani, Liza (Universitas Jember, 2021)
STMIK Umel Mandiri as one of the universities in Jayapura is still less well known, apart from being relatively new in its age and the location of the campus building which is blocked by buildings. So that people sometimes do not know the exact location of the campus. To promote the campus, one of the advertising media used is brochures. Along with current technological developments, augmented reality technology has emerged which is able to combine 2 (two) realities, namely the real and virtual world. When used in brochures, it can provide a feel and experience for readers. So that promoting goods or services can be done more interactively, as well as providing more information to consumers about the product. This augmented reality technology is then used as a solution to the problems faced by STMIK Umel Mandiri in promoting its educational institutions. The purpose of this research is to produce an android application that can display a 3 (three) dimensional brochure model by utilizing augmented reality technology so that it can help the public to get to know the campus to be chosen well. The research method has several stages, namely collecting data about the needs of prospective new students regarding information about the STMIK Umel Mandiri campus, then making a 3 (three) dimensional model of the STMIK Umel Mandiri Campus Building. Then next, do the design of compatible augmented reality on smartphone devices using the Android operating system, and produce 3 (three) dimensional augmented reality objects. This research produces an application based on augmented reality technology that is used to help promote the STMIK Umel Mandiri Campus through devices with the android operating system.